2017
DOI: 10.1038/s41467-017-01649-3
|View full text |Cite
|
Sign up to set email alerts
|

Label-free automated three-dimensional imaging of whole organs by microtomy-assisted photoacoustic microscopy

Abstract: Three-dimensional (3D) optical imaging of whole biological organs with microscopic resolution has remained a challenge. Most versions of such imaging techniques require special preparation of the tissue specimen. Here we demonstrate microtomy-assisted photoacoustic microscopy (mPAM) of mouse brains and other organs, which automatically acquires serial distortion-free and registration-free images with endogenous absorption contrasts. Without tissue staining or clearing, mPAM generates micrometer-resolution 3D i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 33 publications
0
115
0
Order By: Relevance
“…For 25 years, PA imaging has been an active area and is now one of the hottest topics in biomedical optics. PA tomography (PAT) and microscopy (PAM) have numerous diagnostic applications [9][10][11], providing both endogenous [12][13][14][15] and exogenous molecular contrast in structural and functional images [15][16][17]. In particular, PA spectroscopy has produced functional images in the brain and heart [10,[18][19][20], and molecular images using the unique spectra of nanoengineered contrast agents [16,[20][21][22].…”
Section: Mainmentioning
confidence: 99%
“…For 25 years, PA imaging has been an active area and is now one of the hottest topics in biomedical optics. PA tomography (PAT) and microscopy (PAM) have numerous diagnostic applications [9][10][11], providing both endogenous [12][13][14][15] and exogenous molecular contrast in structural and functional images [15][16][17]. In particular, PA spectroscopy has produced functional images in the brain and heart [10,[18][19][20], and molecular images using the unique spectra of nanoengineered contrast agents [16,[20][21][22].…”
Section: Mainmentioning
confidence: 99%
“…This sequence is repeated to obtain a 3D image. The mPAM system currently provides a lateral resolution of 0.91 μm 4 , more than sufficient to image individual cell nuclei without labeling. Moreover, our mPAM system can handle organs of various sizes because it is implemented in reflection mode.…”
Section: Microtomy-assisted Photoacoustic Microscopy (Mpam)mentioning
confidence: 99%
“…Most absorbed light energy will be converted into heat, which results in an acoustic pressure rise propagating as ultrasound-the signal source for PA. PAM in reflection mode is applicable to large tissue volumes. Combined with a microtome for serial removal of previously imaged tissue sections, PAM performs well as a tool for imaging biomolecules of interest in an unstained organ at subcellular resolution 4 . Furthermore, PAM's label-free nature enables it to image differently embedded organs for different applications, e.g., paraffin and agarose are the most common embedding materials used in conventional histology and neuroscience, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To address all of these challenges, in previous studies, our lab developed ultraviolet photoacoustic microscopy (UV-PAM), which provides label-free and high contrast images of DNA/ RNA in cell nuclei with greater imaging depth than a conventional histological image. [31][32][33][34] UV light absorption at 266 nm by DNA/RNA is an order of magnitude higher than that by other biomolecules, such as lipids or proteins. 31,32 We demonstrated that UV-PAM was able to provide analysis of the same quality as postoperative histological analysis and that it required less time.…”
Section: Introductionmentioning
confidence: 99%